Servant Leadership dalam Meningkatkan Prestasi dan Loyalitas Siswa - Nikmah, Ulfa Ainun (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This research is urgent with the background of leaders in educational institutions who serve as role models and motivators, protecting both teachers and students and can have a positive impact. Students are motivated by being active and diligent in studying so that they achieve both academic and non-academic achievements. This research aims to determine the form of servant leadership and its impact in increasing student achievement and loyalty. The method used is descriptive qualitative with a case study approach as well as interview, observation and documentation techniques. The results obtained in this study show that servant leadership by the principal is demonstrated by a character that meets the needs of teachers and students, is empathetic, is a good listener, a capable guide, and builds a healthy group and a good school climate. So that it has an impact on increasing student achievement, both academic and non-academic, up to the national level.